Labour market effects of wage inequality and skill-biased technical change in Germany - Hutter, Christian; Weber, Enzo (Nürnberg, 2017)
"This paper analyses the relationship between wage inequality and labour market development. Relevant economic theories are ambiguous, just as public debates. We measure the effects of wage inequality, skill-biased and skill-neutral technology on hours worked, productivity and wages in a novel structural vector error correction framework identified by non-recursive long-run restrictions. Results show that skill-biased technology shocks reduce hours worked but increase inequality, productivity and wages. Structural inequality shocks also have a negative impact on hours worked, but additionally reduce productivity. We find relevant effects of inequality both above and below the median wage."